Chest imaging cases - Bhalla, Sanjeev; Javidan-Nejad, Cylen; Cummings, Kristopher W. (Cases in radiology., 2012)
Chest Imaging Cases thoroughly encompasses the field of thoracic radiology through 137 cases covering common and challenging radiologic and clinical issues. The cases are divided into categories important for board examinations and clinical practice: diagnoses that should be made on radiography, trachea, esophagus, chest wall, thoracic outlet, congenital lesions, mediastinal lesions, pleura, diaphragm, pulmonary masses, diffuse lung disease, pulmonary vascular disease, thoracic trauma, and post-surgical complications.